Functional and cognitive rehabilitation interventions during intensive care admission: A protocol for a systematic integrative review. Issue 5 (17th February 2023) - Collet, Marie Oxenbøll; Laerkner, Eva; Jensen, Janet; Egerod, Ingrid; Christensen, Jan; Jørgensen, Niels Kasper; Kjærgaard, Rikke Schmidt; Olausson, Sepideh; Wøien, Hilde; Lange, Theis; Nielsen, Anne Højager; Kjær, Maj‐Brit Nørregaard; et al.
Abstract: Background: Long‐term cognitive impairment occurs in up to 60% of intensive care unit (ICU) survivors. Early use of functional and cognitive rehabilitation interventions, while patients are still in ICU, may reduce cognitive decline. We aim to describe the functional and cognitive interventions used during the ICU stay, the healthcare professionals providing interventions, and the potential impact on functional and cognitive rehabilitation. Method: In this integrative systematic review, we will include empirical qualitative, quantitative, mixed‐ and multiple‐methods studies assessing the use of functional and cognitive rehabilitation provided in ICU. We will identify studies in relevant electronic databases from 2012 to 2022, which will be screened for eligibility by at least two reviewers. Literature reported as narrative reviews and editorials will be excluded. We will assess the impact of interventions evaluating a cognitive and functional function, quality of life, and all‐cause mortality at 6–12 months after ICU discharge. The Revised Cochrane risk‐of‐bias Tool will be used for assessing risk of bias in clinical trials. For observational studies, we will use the National Institutes of Health Quality Assessment tool for Observational Cohort and Cross‐Sectional Studies. Furthermore, we will use the critical appraisal skills programme for qualitative studies and the mixed methods appraisal tool for mixed methods studies. We will construct four matrices, including results describing which ICU patients and healthcare professionals were engaged in rehabilitation, which interventions were included in early rehabilitation in ICU, the potential impact on patient outcomes of rehabilitation interventions provided in ICU and a narrative synthesis of themes. A summary of the main results will be reported using modified GRADE methodology. Impact: This integrative review will inform the feasibility randomised clinical trial testing the development of a complex intervention targeting functional and cognitive rehabilitation for patients in ICU.